The model minority stereotype : demystifying Asian American success - Hartlep, Nicholas Daniel (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Researchers, higher education administrators, and high school and university students desire a sourcebook like The Model Minority Stereotype: Demystifying Asian American Success. This second edition of has updated its contents that will assist readers in locating research and literature on the model minority stereotype. This sourcebook is composed of an annotated bibliography on the stereotype that Asian Americans are successful. The most powerful resource for scholars to use and teachers to read must not simply duplicate what others (and previous literature) have written about but must challenge it. Each chapter in The Model Minority Stereotype is thematic and challenges the model minority stereotype. Consisting of an eleventh and updated chapter, this book is the most comprehensive book written on the model minority myth to date"--